Structural Deformation Analysis Design Using Global Positional System (GPS) Satellite Data - Supian, Nor Atikaah Suhaida (IRC, 2019)
Over the past decade, bridge had become one of the important infrastructures in the world’s cities and towns. It accelerates the development and economic growth and considered as a vital link in transport network. However, bridge deformation can occur due to factors such as traffic load, changes of ground water table, temperature and environmental elements.